The View From Coyaba - Abrahams, Peter (My University, 1984)
Manuscript The View From Coyaba
612 pgs. Typescript, letter-sized, sepia-toned, Faily good condition.
Keywords: Taino Indians; Jamaica - History - Taino; Africa; Southern State; Black People; Caribbean People; African American